TRADITION AND TRADITIONS IN THE ORIENTAL CHURCHES: A CRITICAL APPROACH - Khoury, Rafiq (Asian Horizons, 2014)
This article deals with the importance and the richness of the oriental patrimony, in a particular way in the context of the oriental Churches of the Middle East and their societies. But, at the same time, it draws our attention to its dangers, due to a fixist way of dealing with it, which prevents the oriental Churches from facing the present time and its challenges, as it prevents them from taking part in the process of developing their societies. The oriental patrimony is called to develop its large possibilities in shaping today the vocation and the mission of the oriental Churches. That takes place when they actualize their patrimony according to the needs and the aspirations of the oriental Churches today. In that context, the oriental patrimony could be a positive factor in the ecumenical movement, in the mission of these Churches, a creative element in the building up of their societies, and a real, effective and dynamic presence in their societies. In this way, this patrimony can be a memory and a prophecy.